The γ isoform of CaM kinase II controls mouse egg activation by regulating cell cycle resumption - Backs, Johannes; Stein, Paula; Backs, Thea; Duncan, Francesca E.; Grueter, Chad E.; McAnally, John; Qi, Xiaoxia; Schultz, Richard M.; Olson, Eric N. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Fertilization triggers a rise in intracellular Ca2+ concentration ([Ca2+]i) in the egg that initiates a series of events known as egg activation. These events include cortical granule exocytosis that establishes a block to polyspermy, resumption of meiosis, and recruitment of maternal mRNAs into polysomes for translation. Several calcium-dependent proteins, including calcium/calmodulin-dependent protein kinase II (CaMKII), have been implicated in egg activation. However, the precise role of CaMKII in mediating specific events of egg activation and the identity of the isoform(s) present in mouse eggs have not been unequivocally established. Through targeted deletion of the γ isoform of CaMKII, we find that CaMKIIγ is the predominant CaMKII isoform in mouse eggs and that it is essential for egg activation. Although CaMKIIγ−/− eggs exhibit a normal pattern of Ca2+ oscillations after insemination and undergo cortical granule exocytosis, they fail to resume meiosis or to recruit maternal mRNAs. Surprisingly, we find that the recruitment of maternal mRNAs does not directly depend on CaMKII, but requires elevated [Ca2+]i and metaphase II exit. We conclude that CaMKIIγ specifically controls mouse egg activation by regulating cell cycle resumption.
veröffentlicht Dezember 29, 2009
Gesehen am 29.11.2022